2015
DOI: 10.18535/jmscr/v3i9.17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pre and Post Operative Corneal Astigmatism following Pterygium Excision and Conjunctival Autograft

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…In our study, the maximum number of patients belonged to grade 2(90.32%). Similar to this, Gahlot A et al Maheshwari S et al and Shelke et al also found the maximum number of patients belonging to Grade II pterygium 25,26,10 . However, Bhargava P et al found only 23.07 % of patients had grade II pterygium in their study 27 .…”
Section: Figure 1: Change In Astigmatism Preoperatively and Postoperativelysupporting
confidence: 76%
“…In our study, the maximum number of patients belonged to grade 2(90.32%). Similar to this, Gahlot A et al Maheshwari S et al and Shelke et al also found the maximum number of patients belonging to Grade II pterygium 25,26,10 . However, Bhargava P et al found only 23.07 % of patients had grade II pterygium in their study 27 .…”
Section: Figure 1: Change In Astigmatism Preoperatively and Postoperativelysupporting
confidence: 76%
“…These observations were similar to the studies performed by Yousuf, 2005;Saleem et al, 2011;Shelke et al, 2014;Garg et al, 2019. BCVA in all grades of pterygium significantly improved following surgical excision at four months which are in correlation with previous studies (Mohite et al, 2017;Shastry et al, 2019). However, some studies reported improvement in BCVA only in 50-60% cases (Bhargava et al, 2015;Gahlot et al, 2015) or no improvement (Malik et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies proposed that keratometry is not a very useful tool to evaluate the corneal surface changes in pterygium because flattening of peripheral cornea is more than central cornea; hence the keratometry which measures only the central cornea can give rise to imprecise results. (Maheshwari, 2007;Radadia, 2014;Parajuli & Bajracharya, 2019) Excision of pterygium with autologous conjunctival graft is considered the gold standard and most preferable choice of treatment for the management of pterygium (Gahlot et al, 2015;Parajuli & Bajracharya 2019). Results of these studies indicate that surgical excision of pterygium with conventional conjunctival autograft technique is associated with significant decrease in corneal astigmatism postoperatively; however, a study done by Cano-Parra et al, 2002 reported that after excision of pterygium no significant difference was found between pre and post-operative astigmatism values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation